Framtagande av utbildningsmaterial hos The Absolut Company: För de som ska arbeta med coboten - Jeppsson, Gabriel (My University, 2019)
At a constantly growing company in a competitive market, it is important that the technological development is up to date. Another thing that is important for the company is the staffs knowledge and education regarding the newer technologies. Without that knowledge, the production and safety at the workplace can get worse. For this to not occur an education has, in this study, been created for a Swedish liquor company. The company has started using cobots in their production. So, an education is needed for their operators and mechanics. The purpose of the education is to provide a basic understanding of what a cobot is, where and why it is used, how the collaborative work takes place, and to understand the security risks that may occur. This education includes a workshop and a presentation. Methods such as "Problem-Based Learning" and "Learning Pyramid" has been used. Open conversations with operators and a survey at the beginning and end of the education, has contributed to a better understanding of the targeted group. Own learning about the cobots programming and security has been self-taught. This has been done by using "Problem-Based Learning" and reading a technical specification. An operation where a cobot could work has been studied at the factory. And a program has fitting the operation has been done. The completed education contains a presentation and workshop. It has been implemented four times and has improved each time. The material has been further educated to the company so that they can continue with the education. The education has been made for a maximum of 4 operators/mechanics this is due to the number of cobots at the workshop sessions. The layout can be changed. For example, the presentation and the workshop can be held on separate occasions. Hence, the presentation can be held for more operators simultaneously.